Design and Implementation of A Dual-Axis Solar Tracking System using Arduino Uno Microcontroller - Pardosi, Cristoni Hasiholan; Siregar, Marsul; Pandjaitan, Lanny W. (P3M Politeknik Negeri Banjarmasin, 2024)
This paper presents a dual-axis solar tracking system developed and evaluated using LDR sensors and stepper motors, controlled by an Arduino Uno microcontroller. The aim was to enhance photovoltaic energy efficiency by designing a system capable of automatically adjusting the position of solar panels to follow the sun's movement throughout the day. Comparative testing between static solar panels and those equipped with solar trackers demonstrated that the latter produced 35% more power on average. Additionally, the dual tracking system showed a 14% improvement in efficiency over previous averages noted in existing references. Analysis of azimuth and elevation angles confirmed that the solar tracker accurately adjusted the panels' position, significantly boosting solar energy capture. This finding is consistent with prior research, which also supports the efficacy of solar trackers in enhancing photovoltaic efficiency. Future research should expand testing to include various weather and environmental conditions and focus on developing more advanced control algorithms to enhance system responsiveness. Continuous advancements in solar tracking technology are vital for maximizing solar energy potential and facilitating a transition to a more sustainable society.